Building a Strong Clinical Sociology Program through Accreditation (Clinical Sociology Review, 2023)
Existing international clinical sociology undergraduate and graduate programs or programs in a related field with a clinical sociology concentration or track should consider the Commission on the Accreditation of Programs in Applied and Clinical Sociology (CAPACS) to increase the marketability of graduating sociology students.  The Commission works collaboratively with interested program faculty and staff to professionalize the discipline.  Students graduating from a program that is CAPACS accredited makes use of sociological theory and research methods; and students must complete a meaningful practice experience so that they are exposed to professional orientation and ethics.
Keywords: program accreditation; clinical sociology; Commission on the Accreditation of Programs in Applied and Clinical Sociology